Co-release of glutamate and GABA from single vesicles in GABAergic neurons exogenously expressing VGLUT3 - Zimmermann, Johannes; Herman, Melissa; Rosenmund, Christian (Frontiers in Synaptic Neuroscience, 2015)
The identity of the vesicle neurotransmitter transporter expressed by a neuron largely corresponds with the primary neurotransmitter that cell releases. However, the vesicular glutamate transporter subtype 3 (VGLUT3) is mainly expressed in non-glutamatergic neurons, including cholinergic, serotonergic, or GABAergic neurons. Though a functional role for glutamate release from these non-glutamatergic neurons has been demonstrated, the interplay between VGLUT3 and the neuron’s characteristic neurotransmitter transporter, particularly in the case of GABAergic neurons, at the synaptic and vesicular level is less clear. In this study, we explore how exogenous expression of VGLUT3 in striatal GABAergic neurons affects the packaging and release of glutamate and GABA in synaptic vesicles. We found that VGLUT3 expression in isolated, autaptic GABAergic neurons leads to action potential evoked release of glutamate. Under these conditions, glutamate and GABA could be packaged together in single vesicles release either spontaneously or asynchronously. However, the presence of glutamate in GABAergic vesicles did not affect uptake of GABA itself, suggesting a lack of synergy in vesicle filling for these transmitters. Finally, we found postsynaptic detection of glutamate released from GABAergic terminals difficult when bona fide glutamatergic synapses were present, suggesting that co-released glutamate cannot induce postsynaptic glutamate receptor clustering.